Authenification scheme based on fingerprint images - Bắc, Lê Hoài; Hưng, Nguyễn Kim; Ngân, Lê Thị Hoàng (Journal of Computer Science and Cybernetics, 2012)
Digital Watermarking is the art of hiding copyright information to protect host signal from illegal activities. The embedded data can be author identification, company logo and authentication information, and so on. In this paper, we proposed a novel scheme in which biometrics watermark, namely fingerprint is used. Because of specific features of fingerprint, to achieve perfect authentication scheme which meets three criteria of watermarking problem, we utilize some techniques like Gabor algorithm, locally adaptive thresholding, Hilditch's thinning method together with heuristic rules, and Hamming measurement. Furthermore, to make our scheme robustness, the lowest frequency of DCT blocks is chosen and embedded information. With proposed scheme, the authentication scheme can achieve high capacity and good quatily. The experimental results show that our algorithm can be robustness against to JPEG compression, brightness and contract modification, Gaussian noise, adding blur, cropping, rotation, scale, translation, edge detection, emboss, bulge image.